2011
DOI: 10.1007/s00415-010-5896-6
|View full text |Cite
|
Sign up to set email alerts
|

123I-MIBG cardiac uptake and smell identification in parkinsonian patients with LRRK2 mutations

Abstract: Reduced uptake of 123I- metaiodobenzylguanidine (MIBG) on cardiac gammagraphy and impaired odor identification are markers of neurodegenerative diseases with Lewy bodies (LB) as a pathological hallmark, such as idiopathic Parkinson’s disease (IPD). LRRK2 patients present with a clinical syndrome indistinguishable from IPD, but LB have not been found in some cases. Patients with such mutations could behave differently than patients with IPD with respect to MIBG cardiac uptake and olfaction. We studied 14 LRRK2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 40 publications
4
12
0
Order By: Relevance
“…However, the accuracy of the RBDSQ for RBD is not 100%, and it is possible that using polysomnography, the gold standard diagnostic tool for RBD, might have led to different results. A number of previous studies have noted that olfactory function is better in LRRK2-associated PD than iPD 1,4,6,[10][11][12][13] and we have found the same.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, the accuracy of the RBDSQ for RBD is not 100%, and it is possible that using polysomnography, the gold standard diagnostic tool for RBD, might have led to different results. A number of previous studies have noted that olfactory function is better in LRRK2-associated PD than iPD 1,4,6,[10][11][12][13] and we have found the same.…”
Section: Discussionsupporting
confidence: 86%
“…1 Establishing differences between LRRK2-associated PD and idiopathic PD (iPD) may provide clues to the molecular pathogenesis of specific features of Parkinson's disease in that those that differ may relate to the function of the LRRK2. The phenotype of LRRK2-related PD has been described as broadly consistent with idiopathic Parkinson's disease, but the phenotype of LRRK2-associated PD has been described as more slowly progressive from the motor perspective, 1 with less autonomic, 2-6 cognitive, [1][2][3][7][8][9] and olfactory 1,4,6,[10][11][12][13] dysfunction. On the other hand, a high frequency of anxiety and depressive symptoms has been noted.…”
mentioning
confidence: 99%
“…A pilot study in 10 individuals with leucine‐rich repeat kinase 2 (LRRK2)‐PD found HRV was not reduced in LRRK2 ‐PD, suggesting a relative sparing of cardiac autonomic innervation . This observation is supported by several studies demonstrating relatively preserved cardiac 123 I‐MIBG uptake in LRRK2 ‐PD . The present study extends these findings in a larger group of patients to determine whether HRV is altered in LRRK2 ‐PD as well as in nonmanifesting carriers and related noncarriers when compared with iPD and unrelated healthy controls.…”
supporting
confidence: 86%
“…22 This observation is supported by several studies demonstrating relatively preserved cardiac 123 I-MIBG uptake in LRRK2-PD. [23][24][25][26][27] The present study extends these findings in a larger group of patients to determine whether HRV is altered in LRRK2-PD as well as in nonmanifesting carriers and related noncarriers when compared with iPD and unrelated healthy controls.…”
supporting
confidence: 59%
“…It could be either a lighter load of synuclein deposition, or it may be factors other than synuclein that are pathologically different. It has been argued that an association of olfactory loss and I-metaiodobenzylguanidine cardiac uptake segregating together in a study of LRRK2 mutation carriers supports presence of Lewy body pathology in this group 13. If synuclein deposition detectable on autopsy was solely responsible for mediating the olfactory deficit, then most nonmutation PD should demonstrate hyposmia, as the majority of autopsy cases of nonmutation PD report both nigral degeneration and brainstem Lewy bodies 34.…”
Section: Discussionmentioning
confidence: 99%